2014
DOI: 10.1111/jace.13148
|View full text |Cite
|
Sign up to set email alerts
|

Prediction on the Surface Phase Diagram and Growth Morphology of Nanocrystal Ruthenium Dioxide

Abstract: Surface energy has an important role in controlling the exposed facets and growth morphology of nanocrystals. In this study, we employed first‐principle thermodynamic modeling and calculations to evaluate the substantial effects of environmental factors (temperature and oxygen partial pressure), on the surface structure, stability, and nanocrystal morphology of rutile‐type ruthenium dioxide (RuO2). Both stoichiometric and nonstoichiometric surfaces with ideal bulk terminations were assessed. The relative order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…For charge integration, the reverse sweep was used given the ease of subtracting the double-layer background. Surprisingly, for the facet with the lowest surface energy (110), 32 activity was higher in 0.1 M HClO 4 than in KOH, similar to that previously reported for nanoparticles ( Figure S14) 5 and in contrast to that expected given the negligible super-Nernstian shift of Ru redox. A slight increase in the activities with cycling or potential holding, however, suggested potential instability.…”
Section: Electrochemical Measurementssupporting
confidence: 87%
“…For charge integration, the reverse sweep was used given the ease of subtracting the double-layer background. Surprisingly, for the facet with the lowest surface energy (110), 32 activity was higher in 0.1 M HClO 4 than in KOH, similar to that previously reported for nanoparticles ( Figure S14) 5 and in contrast to that expected given the negligible super-Nernstian shift of Ru redox. A slight increase in the activities with cycling or potential holding, however, suggested potential instability.…”
Section: Electrochemical Measurementssupporting
confidence: 87%
“…A RuO 2 (110) facet was selected as a model of the RuO 2 /water interface because it has been detected by nanoparticle XRD analyses and since it has been determined to possess the lowest surface energy by DFT calculations . Furthermore, an oxygen covered (1 × 2) structure was used as a reference system for the RuO 2 /water interface because it is experimentally detected under the electrode potential close to oxygen evolution…”
Section: Methodsmentioning
confidence: 99%
“…[15][16][17] It was found that at ambient conditions the most stable RuO2 surface has (110) crystallographic orientation. 18 However, the atomic structure and even the composition of the surface can be changed under different environmental conditions (temperature and partial pressure of oxygen). 18 Several theoretical predictions of possibly stable terminations of (110)-RuO2 surface were made by Reuter et al 19,20 Scanning tunneling microscopy (STM) is often used to study surfaces of materials.…”
Section: Introductionmentioning
confidence: 99%
“…18 However, the atomic structure and even the composition of the surface can be changed under different environmental conditions (temperature and partial pressure of oxygen). 18 Several theoretical predictions of possibly stable terminations of (110)-RuO2 surface were made by Reuter et al 19,20 Scanning tunneling microscopy (STM) is often used to study surfaces of materials. 15 However, it shows only the top layers of the materials and in a case of RuO2 only oxygen can be distinguished.…”
Section: Introductionmentioning
confidence: 99%